Business elites and the process of democratization in Paraguay - Luis Ortiz-Sandoval; Guillermo Rojas (Íconos, 2019)
This study exposes the first phase of the process of democratization in Paraguay that began in 1987 and ended in 1992. It was based on a sociohistorical approach that used qualitative information from testimonies about the process in question, as well as descriptive statistical information that helped explain the context of the changes that took place in the referred period. From this framework, the paper exposes how the Paraguayan business elites, as the most dynamic sector of the ruling class, not only led the removal of the authoritarian regime of the ex-dictator Alfredo Stroessner, but also guided the economic management and the redesign of the institutional architecture of the republic according to their interests and the privileges obtained during the dictatorship. Among the findings, this research shows that during the "first transition" these elites created mechanisms of accommodation and neutralization of the advances in social rights, to the extent that these would imply a substantive democratization of the political system. Although the democratic aperture was presented as a necessary change, it had risky implications due to the promotion of the specific interests of the elites. In conclusion, democracy was marked by the seizure of the State by the economic sectors that were strengthened after the authoritarian regime, leaving the working classes weakened in their ability to resist and access rights.